2020
DOI: 10.3390/brainsci10040246
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of High-Definition Transcranial Direct Current Stimulation on Foot Muscle Strength, Passive Ankle Kinesthesia, and Static Balance: A Pilot Study

Abstract: This study aimed to examine the effects of single-session anodal high-definition transcranial direct current stimulation (HD-tDCS) on the strength of intrinsic foot muscles, passive ankle kinesthesia, and static balance. Methods: In this double-blinded self-controlled study, 14 healthy younger adults were asked to complete assessments of foot muscle strength, passive ankle kinesthesia, and static balance before and after a 20-minute session of either HD-tDCS or sham stimulation (i.e., control) at two visits se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 46 publications
(60 reference statements)
0
36
0
Order By: Relevance
“…Current intensity of the anode was set to 2 mA; return of current was evenly distributed between the four cathodes. Neuro-modeling results indicated that this montage induced electric fields that penetrated deep into the lower-extremity area of the primary sensorimotor cortex located along the longitudinal fissure [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Current intensity of the anode was set to 2 mA; return of current was evenly distributed between the four cathodes. Neuro-modeling results indicated that this montage induced electric fields that penetrated deep into the lower-extremity area of the primary sensorimotor cortex located along the longitudinal fissure [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three studies used conventional tDCS applied over the sensorimotor cortex with an electrode size of 35 cm 2 (Tanaka et al, 2009 ; Zhou et al, 2018 ; Yamamoto et al, 2020 ). One study used a 4 × 1 ring high-definition tDCS (HD-tDCS), in which the anodal electrode was placed over Cz and was surrounded by four cathodal electrodes with a size of 1 cm 2 (Xiao et al, 2020 ). Three studies applied the current intensity of 2 mA (Tanaka et al, 2009 ; Zhou et al, 2018 ; Xiao et al, 2020 ), and one study applied the intensity of 1.5 mA (Yamamoto et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study used a 4 × 1 ring high-definition tDCS (HD-tDCS), in which the anodal electrode was placed over Cz and was surrounded by four cathodal electrodes with a size of 1 cm 2 (Xiao et al, 2020 ). Three studies applied the current intensity of 2 mA (Tanaka et al, 2009 ; Zhou et al, 2018 ; Xiao et al, 2020 ), and one study applied the intensity of 1.5 mA (Yamamoto et al, 2020 ). The duration of tDCS was 10 min in two studies (Tanaka et al, 2009 ; Yamamoto et al, 2020 ) and 20 min in the other two studies (Zhou et al, 2018 ; Xiao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other non-invasive methods of neuromodulation, such as prismatic adaptation, have been shown to activate compensatory postural adjustments to achieve improved body stability in the non-neurologically impaired (Bonaventura et al, 2020). Few studies, however, have investigated the effects of tDCS delivered to the leg motor area on balance and postural control in non-neurologically impaired individuals (Craig and Doumas, 2017;Yosephi et al, 2018;Xiao et al, 2020) and even more limited in individuals post-stroke (Sohn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%